Frederick Starr papers - Starr, Frederick, 1858-1933.
Typescripts of journal entries (1927 October 14 and 15), an address welcoming visiting American journalists (1929 June 10), and a plan for local self-government written during a visit to rural Korea.
Anthropologist, author, editor, and educator.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Korea -- Description and travel; Anthropologists; Authors; Editors; Educators